DETERMINAN CUSTOMER SATISFACTION PADA PENGGUNA GOPAY DI KOTA DENPASAR - Ni Wayan Wijayanti; Ni Luh Putu Chandra Kirana; Ni Luh Putu Sariani; Desak Made Sukarnasih (Universitas Mahendradatta, 2022)
This study aims to determine the effect of Experiential Marketing, EService Quality, Sales Promotion partially and simultaneously on CustomerSatisfaction Gopay Users in Denpasar City. Data collection techniques used aquestionnaire. The sample in this study were 75 respondents Gopay users inDenpasar City with the purposive sampling method. The data analysis techniqueusing multiple linear regression. The results of this study indicate thatExperiential Marketing, E-service Quality, Sales Promotion have a positive andsignificant effect partially and simultaneously on Customer Satisfaction Gopayusers in Denpasar City. Suggestions that can be given by researchers tomanagement are to improve experiential marketing so that customer satisfactionfor Gopay users in Denpasar City is achieved.